Evaluation of tungro-resistant lines based on tungro disease severity and agronomic characteristics - Achmad Gunawan; Nur Rosida; Khaerana Khaerana; Arif Muazam; Ani Mugiasih (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
Tungro disease severity and agronomic characteristics of tungro-resistant lines. Tungro is one of the diseases problem in rice production. The simplest approach to solve the problem is to use the resistance tungro variety, which is made of tungro resistance lines. At present, the character of the new type of rice becomes a preference by the formation of a variety. The line with the character of Agronomy is a decisive factor in the choice of a variety by farmers. The aim of this study was to evaluate the potential tungro resistant lines according to severity and agronomy. The research was carried out in the dry season of 2015 in Polewali Mandar, West Sulawesi. Fifty promising tungro lines and four reference varieties were tested using the Augmented Design with five blocks as replicates. Variables observed were green leafhopper population density and the presence of tungro disease. Agronomic character variables observed included clump shape, productive tiller at 90 DAT, flowering age 50%, the weight of 1000 grains, filled and unfilled grain, and grain yield of kg/ha. The results showed that there were several lines that had significantly higher yield potential , i.e. BP3734A-3-15-LRG-5-8-2-5, BP3770A-1-218-LRG-2-3-1-9, BP3840A-6-253-LRG-8-6-2-8, BP3862A-21-1054-LRG-5-1-1-6, BP3866A-4-1207-LRG-9-3-2-7, BP3870A-4-1357-LRG-2-3-1-7 and BP3870A-4-1363-LRG-8-1-1-7. All of these lines have the potential to be processed to the next phase.